Bias correction of nutritional status estimates when reported age is used for calculating WHO indicators in children under five years of age - Amado D Quezada; Armando García-Guerra; Leticia Escobar (Instituto Nacional de Salud Pública, 2016)
Objective.To assess the performance of a simple correction method for nutritional status estimates in children under five years of age when exact age is not available from the data. Materials and methods. The proposed method was ba- sed on the assumption of symmetry of age distributions within a given month of age and validated in a large population-based survey sample of Mexican preschool children. Results. The main distributional assumption was consistent with the data. All prevalence estimates derived from the correction method showed no statistically significant bias. In contrast, failing to correct attained age resulted in an underestimation of stunting in general and an overestimation of overweight or obesity among the youngest. Conclusions. The proposed method performed remarkably well in terms of bias correction of estimates and could be easily applied in situations in which either birth or interview dates are not available from the data.